A new NLR disease resistance gene Xa47 confers durable and broad-spectrum resistance to bacterial blight in rice - Lu, Yuanda; Zhong, Qiaofang; Xiao, Suqin; Wang, Bo; Ke, Xue; Zhang, Yun; Yin, Fuyou; Zhang, Dunyu; Jiang, Cong; Liu, Li; Li, Jinlu; Yu, Tengqiong; et al. (Frontiers in Plant Science, 2022)
Bacterial blight (BB) induced by Xanthomonas oryzae pv. oryzae (Xoo) is a devastating bacterial disease in rice. The use of disease resistance (R) genes is the most efficient method to control BB. Members of the nucleotide-binding domain and leucine-rich repeat containing protein (NLR) family have significant roles in plant defense. In this study, Xa47, a new bacterial blight R gene encoding a typical NLR, was isolated from G252 rice material, and XA47 was localized in the nucleus and cytoplasm. Among 180 rice materials tested, Xa47 was discovered in certain BB-resistant materials. Compared with the wild-type G252, the knockout mutant of Xa47 was more susceptible to Xoo. By contrast, overexpression of Xa47 in the susceptible rice material JG30 increased BB resistance. The findings indicate that Xa47 positively regulates the Xoo stress response. Consequently, Xa47 may have application potential in the genetic improvement of plant disease resistance. The molecular mechanism of Xa47 regulation merits additional examination.